2017
DOI: 10.1590/s1980-220x2016033303271
|View full text |Cite
|
Sign up to set email alerts
|

Incidentes com medicamentos em unidade de urgência e emergência: análise documental

Abstract: Objective:To characterize medication incidents occurred in an outpatient emergency service. Method: Descriptive, documental, retrospective and quantitative research. The International Classification for Patient Safety was the theoretical reference for the construction of the instrument used to collect and analyze the data from 119 notification and investigation forms of incidents occurred in 2014 in a teaching hospital. Data were collected twice, compared, corrected and transcribed to an Excel worksheet. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
0
2
0
18
Order By: Relevance
“…Observou-se que a frequência de notificação de erros foi maior para faixa etária acima de 60 anos, o que corrobora com achados de outros estudos em que os eventos adversos relacionados a medicamentos vêm sendo citado como os incidentes de segurança mais frequentes na população idosa (Maher, Hanlon & Hajjar, 2014;Newbould et al, 2017), sendo que as principais causas apontadas são: idade avançada, múltiplas doenças e polifarmácia (Valle, Cruz, & Santos, 2017).…”
Section: Discussionunclassified
“…Observou-se que a frequência de notificação de erros foi maior para faixa etária acima de 60 anos, o que corrobora com achados de outros estudos em que os eventos adversos relacionados a medicamentos vêm sendo citado como os incidentes de segurança mais frequentes na população idosa (Maher, Hanlon & Hajjar, 2014;Newbould et al, 2017), sendo que as principais causas apontadas são: idade avançada, múltiplas doenças e polifarmácia (Valle, Cruz, & Santos, 2017).…”
Section: Discussionunclassified
“…Nos hospitais do estudo verificou-se perfil divergente nas notificações das metas estabelecidas pelos órgãos reguladores do Brasil. A prevalência de erros associados à medicação foi maior no hospital de trauma, assim como encontrado em outras unidades de urgência do Brasil, sendo mais baixo em hospitais e unidades que não tem esse perfil assistencial [16][17][18]. As características assistenciais das unidades de urgência podem contribuir para os erros relacionados a administração de medicamentos, se medidas gerenciais com foco na assistência e no risco não forem adotadas [17].…”
Section: Discussionunclassified
“…Essa falha não foi notificada nos hospitais estudados. Em UTI, no centro-oeste, 11,2% das notificações estavam relacionadas a complicações cirúrgicas [17]. As falhas de comunicação foram 9% em hospital de Botucatu [13].…”
Section: Discussionunclassified
“…Scientific evidence shows that medication errors, particularly those involving potentially dangerous parenteral drugs, are the most common safety incidents in urgent care services, ICUs, and surgical units, and that the majority of these incidents involve nursing staff (21) . A study conducted in a pediatric cardiothoracic intensive care unit in a hospital in the United States showed that medication errors resulting in patient harm were reduced by initiating quality improvement interventions that included nursing education.…”
Section: Discussionmentioning
confidence: 99%